Decentralized urban runoff recycling facility addressing the security of the water-energy-food nexus - Macedo, Marina Batalini de (2020)
Low Impact Development (LID) practices are low-cost adaptation alternatives to assist traditional drainage systems, aiming at mitigating the risks of hydrological extremes. In this project, a new nomenclature is used for LID, facing the extremes due to change in future scenarios and their adaptations. For example, when they are adapted for changes in land use and occupation, e.g. urbanization, they are called 1st generation LID (LID-1G). When incorporating adaptations of land use and climate change, they are called 2nd generation (LID-2G). Also, when the adaptation incorporates the recycling of resources for water-energy-food security, they are called 3rd generation (LID-3G). However, scientific gaps still remain because: few studies evaluate the combined qualitative and quantitative efficiency of LID-1G and LID-2G; for LID-3G, there is limited knowledge about incorporating climate change scenarios and resource recycling to reduce water-energy-food security risks; these gaps are still larger in areas of subtropical climate and when applied in a decentralized way. Therefore, this doctoral research enhances a new theoretical-experimental framework on a new LID-3G of bioretention, for decentralized use. The methodology addresses three stages: (1) analysis of design incorporating future scenarios with drivers of change of urbanization and climate; (2) new criteria for operation, maintenance and runoff volume and water quality monitoring for 3rd generation, in field scale and laboratory scale, (3) proposition and study of new evaluation coefficients aiming at resources recycling, contribution to water-energy-food security and local sustainability. The results were discussed under conditions of: (a) subtropical climate, (b) Brazilian urbanization standards, and (c) social demands for water-energy-food security.